Advancing the mechanistic understanding of corrosion in supercritical CO2 with H2O and O2 impurities. (1st April 2023) - Li, Kaiyang; Zeng, Yimin
Abstract: The effects of impurities H2 O and O2 in transported s-CO2 on the corrosion modes and kinetics of pipeline steels were investigated using rotating cage methodology and in-situ electrochemical noise (EN) technique in an autoclave. In s-CO2 with H2 O and O2, pressure acts as a key factor on the solubility of H2 O in s-CO2 and corrosion extents, and there is a threshold pressure (∼10 MPa) above which corrosion rate remarkably increases with pressure. In-situ EN results in different CO2 environments further reveal that corrosion in s-CO2 with H2 O and O2 is dominated by gas chemical reactions rather than electrochemical reactions. Highlights: Impurities H2 O and O2 in s-CO2 only have a moderate effect on corrosion. Pressure is a key factor by controlling the H2 O solubility in s-CO2. Corrosion remarkably increases when pressure > 10 MPa due to increased H2 O content. In-situ EN technique is developed for exploring corrosion modes in s-CO2. Corrosion in H2 O-saturated s-CO2 + O2 is dominated by gas chemical reactions.